IMAGES OF CONTROL OVER BLACK WOMEN IN THE TV SOAP OPERA VALE TUDO (2025) - Claudino, Gabriela Caroline Alves; Claudino, Alessandra Helen Alves (Seven Editora, 2026)
This study aims to analyze the representations of the characters Raquel Acioli and Maria de Fátima from the soap opera Vale Tudo (2025), considering the dialogue with Black feminist discussions on images of control (COLLINS, 1990). The discussion established a relationship between the ways these Black women are represented in the soap opera and the stereotypes associated with this social group. The intention is to promote debate about the relevance of soap operas in addressing social issues and about the social imaginary that has been constructed around Black women.